A Slope-Adapted Sample-Tilting Method for Profile Measurement of Microstructures with Steep Surfaces. (13th August 2015) - Fang, Hui; Xu, Bin; Chen, Wei; Tang, Hairong; Zhao, Shiping
Abstract : This paper presents a slope-adapted sample-tilting method for the profile measurement of microstructures with steep surfaces. Distinct from the traditional scanning method that has the restriction of a maximum detectable angle, this method corrects the sample-stylus relative angle during the measurement of the steep surface to eliminate the profile deviation and the scanning blind region. The performance of the proposed method was verified by simulations that measured the surface profiles of a trapezoidal microstructure and a spherical microstructure, finding maximum errors of 0.15  μ m and 1.71  μ m, respectively, compared to 3.63  μ m and 7.85  μ m using the traditional scanning method. The proposed method enables accurate profile measurement and quality control of microstructures with steep surfaces.